2022
DOI: 10.1590/0102-311x00149321
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of diabetes in Brazil: prevalence data from the 2013 and 2019 Brazilian National Health Survey

Abstract: The prevalence of diabetes has been growing worldwide. This study aimed to estimate the prevalence of self-reported diabetes in Brazil in 2019, to describe its evolution from 2013, and to evaluate the role of population growth, aging, and other factors in the changes found. The 2019 Brazilian National Health Survey, a nationally representative cross-sectional survey, queried a physician diagnosis of diabetes in a probabilistic multistage cluster sample. The crude prevalence of known diabetes in 2019 was 7.7% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
(11 reference statements)
0
10
0
2
Order By: Relevance
“…The low prevalence of SAH in the sample may be related to the absence of smoking and excessive alcohol consumption (MALTA et al, 2022). The high distribution of DM frequency observed in the sample may be related to a higher risk of overweight and obesity in the elderly METABÓLICA, 2016;REIS et al, 2022), as well as sedentary behavior (BULL et al, 2020;SÁNCHEZ-MARTÍNEZ et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…The low prevalence of SAH in the sample may be related to the absence of smoking and excessive alcohol consumption (MALTA et al, 2022). The high distribution of DM frequency observed in the sample may be related to a higher risk of overweight and obesity in the elderly METABÓLICA, 2016;REIS et al, 2022), as well as sedentary behavior (BULL et al, 2020;SÁNCHEZ-MARTÍNEZ et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…As for the normal glucose level metric, it is worth highlighting that the information obtained based on self-report tends to be less accurate. In fact, another study 26 based on data from the 2019 PNS reported a 24% increase in the prevalence of diabetes mellitus , compared to 2013. Multiple factors contributed to this finding, including an increase in the incidence and diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…The severity risk factors identified in our sample agree with those described in previous studies in the USA, Mexico, Sudan, and China [17][18][19][20][21] . However, an 8-fold increase in the odds of a subject with diabetes progressing to critical stages of the disease with respect to individuals without the condition is alarming, considering that Brazil is in the fifth position in the list of countries with the most significant number of people with diabetes, and has a national prevalence estimative of 7.7% 22,23 .…”
Section: Discussionmentioning
confidence: 99%